Underexplored bacteria as reservoirs of novel antimicrobial lipopeptides - Clements-Decker, Tanya; Kode, Megan; Khan, Sehaam; Khan, Wesaal (Frontiers in Chemistry, 2022)
Natural products derived from microorganisms play a prominent role in drug discovery as potential anti-infective agents. Over the past few decades, lipopeptides produced by particularly Bacillus, Pseudomonas, Streptomyces, Paenibacillus, and cyanobacteria species, have been extensively studied for their antimicrobial potential. Subsequently, daptomycin and polymyxin B were approved by the Food and Drug Administration as lipopeptide antibiotics. Recent studies have however, indicated that Serratia, Brevibacillus, and Burkholderia, as well as predatory bacteria such as Myxococcus, Lysobacter, and Cystobacter, hold promise as relatively underexplored sources of novel classes of lipopeptides. This review will thus highlight the structures and the newly discovered scaffolds of lipopeptide families produced by these bacterial genera, with potential antimicrobial activities. Additionally, insight into the mode of action and biosynthesis of these lipopeptides will be provided and the application of a genome mining approach, to ascertain the biosynthetic gene cluster potential of these bacterial genera (genomes available on the National Center for Biotechnology Information) for their future pharmaceutical exploitation, will be discussed.